Impact of unilateral single-mode balance training vs. combined balance and plyometric training on soccer players` interlimb asymmetry in balance and neuromuscular performance - Muehlbauer, T.; Borgmann, K.; Limpach, S.; Krombholz, D.; Panzer, S. (Frontiers in Sports and Active Living, 2026)
Background: It has been shown that unilateral balance training (BT) enhances balance and neuromuscular performance in the trained and untrained leg and thus has the potential to reduce side-to-side differences. However, it is unresolved how effective unilateral single-mode BT compared to unilateral combined balance and plyometric training (BT + PT) is in reducing interlimb asymmetry. Thus, we examined the impact of both training modalities on soccer players` interlimb asymmetry in balance and neuromuscular performance.